COLLECTIVE POLICY IN AGRICULTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the policy of collectivization in agriculture. It also analyzes the rapid growth of cotton fields as a result of collectivization.